Newly-recognised Continental Fragments Rifted from the West Australian Margin - Williams, SE; Joanne Whittaker; Muller, RD (2013)
The southwest Australian margin formed at the nexus of rifting and breakup between India, Australia and Antarctica in the Early Cretaceous. Studying the basin evolution along this margin has been hampered by a lack of data from the offshore Perth Abyssal Plain (PAP), and from the conjugate Greater Indian margin, which was highly deformed during collision with Eurasia. Here, we present new data (magnetic anomaly profile data, swath bathymetry, and dredge samples) constraining the evolution of the PAP, collected during voyage ss2011/v06 of the RV Southern Surveyor in late 2011. The Batavia Knoll (BK) and Gulden Draak Knoll (GDK) are two prominent, previously unsampled bathymetric features located >1600 km offshore Australia that have been assumed to be igneous features. Successful dredges on the western flanks of both knolls recovered continental basement rocks, revealing that both knolls are microcontinents. We use quantitative analysis of shiptrack magnetic profiles combined with satellite gravity anomalies to estimate the extent and spatial variation in thickness of the continental crust. Sediment thickness estimates are made using depths to magnetic sources for shiptrack profiles. The geophysical data provide evidence for basin structures within the knolls of a similar scale to those imaged within other fragments of stretched continental crust such as the Naturaliste Plateau. Interpretation of previously unidentified M-series anomalies in the Perth Abyssal Plain, combined with dredge data, support a reconstruction model where the BK and GDKs are microcontinents that initially rifted with Greater India during breakup with Australia at ~130 Ma. As seafloor spreading ceased in the PAP at about 105–100 Ma, a westward ridge jump led to the rifting of the BK and GDK from Greater India.